Effects of Policy Environment on Solid Waste Management in Urban Centres in Eastern Uganda - Eumu, Benard; Edaku, Charles; Meza, Faustino L. Orach (International Journal of Public Policy and Administration, 2024)
Purpose: This paper explores the policy environments in urban centres in Eastern Uganda and the extent to which they have affected Solid waste management. Methodology: A correlational survey design was used to analyze primary data from 273 employees of urban centres, using, descriptive statistics, Pearson correlation and regression analysis. Findings: Policy environment positively predicted effective Solid waste management (β =.21, p<.05). Though legal, political, cultural and media limitations decreased effectiveness of Solid Waste Management. Unique Contribution to Theory, Policy, and Practice: Urban authorities should implement more responsive governance that promotes effectiveness, responsiveness and participation of residents and in all SWM operations. Urban councils need to innovate strategies to allow a high degree of organized representation, accessibility and openness for all categories of stakeholders. They also need to develop a variety of initiatives to allow all stakeholders in the communities to actively contribute to SWM ideas for the common good of their areas.